Aportes en la construcción participativa del presupuesto en la municipalidad de Pujilí como una nueva política pública de desarrollo local. - Villacrés Chiriboga, Luis Miguel (2023)
The current study focuses on citizen participation in the budget formulation process in the Pujilí canton, Ecuador. The problem addressed revolves around questioning whether generating contributions in the participatory construction of the Municipal GAD budget in the Pujilí canton will drive the local development of the area. The lack of interest and understanding in budgetary processes, both by the governments and the citizenry, has created a gap in effective participation. This has resulted in a lack of transparency in budget execution and a negative perception of the population toward their leaders. The problem was approached through a deductive approach and a Likert scale-based survey. This instrument underwent a validation process by experts in administration and public policies, and the instrument's reliability was determined through the application of Cronbach's Alpha. Among the main results obtained, it was evident that 90% of respondents considered it necessary to make changes in public policies to strengthen citizen participation in the budgetary process. These findings highlight the opportunity to improve citizen participation and enhance transparency in public management through adjustments to existing policies.